Analisis Vegetasi Mangrove dan Kelimpahan Biota (Crustacea) yang Berasosiasi di Pantai Selatan Kabupaten Manggarai Timur - Rifaldus Dani; I Wayan Arthana; Ni Made Ernawati (Journal of Marine and Aquatic Sciences, 2021)
Mangrove is a typical forest and grows along the coast or river estuaries that are affected by tidal of sea water. The aims are to determine the mangrove vegetation and abundance of associated (Crustacea) in the South Coast of East Manggarai Regency. Important value, density relative, frequency relative, index uniformity and diversity obtained from vegetation analysis used as indicators to describe vegetation structure and mangrove forest diversity as well as the abundance of associated Crustaceans. This research was conducted in mangrove forest in South Beach of East Manggarai Regency in February until March 2017. To support the research, water quality measurement on mangrove forest was conducted. Measurement of water quality is done in situ (temperature, pH and salinity). Methods used in this study the quantitative descriptive. Determination of the sampling done by means of purposive sampling. A kind of the mangrove found to consist of 7 species that Avicennia lanata, Rhizophora mucronata, Ceriops decandra, Bruguiera gymnorrhiza, Sonneratia alba, Sonneratia casiolaris, And Xylocarpus granatum. The diversity category in a low and index mangrove uniformity category in a high. While the Important Value Analysis shows that Avicenia Lanata species have the highest importance compared to other species. The water quality in the South Coast of East Manggarai Regency are still worth to support life and development mangrove. Abundance Crustacea higher at the station I by abundance of 7,6 ind / m2.